PENEGAKAN HUKUM TERHADAP PENAMBANG EMAS ILEGAL DI KECAMATAN CIBEBER KABUPATEN LEBAK BANTEN - Feri Irawan; Rokilah Rokilah; Hasuri Hasuri (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABTRACT This study aims to find out how law enforcement is for gold miners without permits and to find out efforts to overcome law enforcement obstacles for gold miners without permits in Cibeber District, Lebak Regency. Furthermore, the data obtained were analyzed using qualitative techniques and then presented descriptively, namely explaining, describing and describing according to the problems that are closely related to this research. The results of the research and discussion show that: (1) The implementation of law enforcement against illegal gold miners in Cibeber District, Lebak Banten Regency takes three stages of the process, namely: a) The government carries out joint socialization with the police and Indonesion national army regarding Law Number 4 of 2009 b) carry out patrols as a preventive measure to prevent and monitor mining or dompeng activities; c) Carry out criminal prosecution as a form of repressive efforts strictly against the perpetrators of the dompeng. (2) Efforts made to enforce the law on the criminal act of gold mining without a permit are firstly preventive measures. Second, repressive measures. Obstacles in enforcing the law on the crime of gold mining without a permit are limited supporting facilities and infrastructure, lack of concern and legal awareness of the community, problems with coordination with the government.